ANALISIS PERBANDINGAN HUKUM PERDATA INTERNASIONAL DAN HUKUM ISLAM KONTEMPORER TERHADAP TRANSAKSI VALUTA ASING : A Comparative Study of International Civil Law and Contemporary Islamic Law - Aslamiyah, Mujadiddah; Falah, Nabilah; Paqih, Ibnu (Universitas Islam Negeri Alauddin Makassar, 2025)
Foreign currency transactions in Indonesia are regulated by Law of the Republic of Indonesia Number 7 of 2011 concerning Currency, which makes the Rupiah the only legal tender in Indonesia, with exceptions for certain transactions such as international trade and foreign exchange transactions conducted through banks authorized by Bank Indonesia. This study was a normative juridical with a comparative approach that intended to compare two views of private international law and contemporary Islamic law through secondary data sources. The results of the study indicated that in private international law, foreign exchange transactions were regulated by freedom of contract, which limited the application of international legal norms. On the other hand, in Islamic Law, foreign exchange transactions must be carried out with the principle of justice and avoid practices involving usury, maysir (speculation), and gharar (uncertainty). Islamic law recommends that transactions be carried out in cash (spot), which is in accordance with sharia provisions to avoid prohibited speculative elements. Although these two legal systems have different approaches, both aim to ensure fair transactions by applicable provisions. Therefore, in practice, foreign exchange transactions must meet the principles of transparency, fairness, and compliance with existing regulations, both in the national legal system and Islamic law, to avoid practices that are detrimental and inconsistent with applicable laws.